Rusunawa Di Pekanbaru Dengan Penekanan Penghawaan Alami - Umar Hafiz Alfadil; Pedia Aldy; Ratna Amanati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The minimal existing of residences in the city of Pekanbaru is causing the rental price or the selling price of a dwelling unit continues to rise. With the difference of economic ability in each individual, not all the people who are migrants in Pekanbaru city get a place to live. Dense economic growth in downtown Pekanbaru, causing the amount of empty land becomes reduced. Pekanbaru need an affordable solution for a settlement and able to accommodate the density of residents of Pekanbaru city. One of the affordable rental dwelling is a Rusunawa (Rented Simple Public Mansion). This Rusunawa is intended for middle-class people who want to have a fixed residence at a more affordable price. Some facilities that needed in the design of Rusunawa are residential facilities, shared facilities, environmental facilities and supporting/infrastructure facilities. The designing of natural cooling in Rusunawa is by applying 4 elements : wind, space, water & vegetation and building materials. Air circulation in Rusunawa designed to run smoothly because it can maximize the application of natural cooling into the buildings. The application of the concept design is to facilitate Rusunawa with communal space as a means of social interaction among residents. Its application is by making a gathering room, sky bridge and sky plaza, and the building mass into the form of boxes.Kata kunci: Rental house, Rusunawa, Rented Simple Public Mansion, Natural cooling